ChemInform Abstract: Organic Stereochemistry. Part 6. The Conformation Factor in Molecular Pharmacology. Issue 37 (22nd August 2013) - Vistoli, Giulio; Testa, Bernard; Pedretti, Alessandro
Abstract Review: ca. 40 refs.